2014
DOI: 10.4028/www.scientific.net/msf.802.409
|View full text |Cite
|
Sign up to set email alerts
|

Interface Evaluation of MCrAlY Powder Bond Coat on 316 SS Processed with Laser Irradiation

Abstract: As aircraft and thermoelectric turbine blades work in aggressive environments (high temperatures and pressures), they are exposed to oxidation reactions. Ceramic coatings are employed to increase the turbine work temperature (improving its performance) and a bond coat (BC), base of particulate material of Ni-Cr-Al powders, which assure a good adhesion, gradual decrease in thermal expansion coefficient between the metallic substrate and the ceramic top coat, avoiding the oxidation effect in the metallic substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Previews work of Teleginski et. al [9] examined by SEM coatings obtained by laser deposition, and indicated that during the laser treatment of a pre-deposited layer a small portion of the substrate material is also melted, mixing its elements with the coating composition. This mixing results in increased compatibility between the NiCrAlY coating and the substrate, leading to a metallurgical bonding.…”
Section: Resultsmentioning
confidence: 99%
“…Previews work of Teleginski et. al [9] examined by SEM coatings obtained by laser deposition, and indicated that during the laser treatment of a pre-deposited layer a small portion of the substrate material is also melted, mixing its elements with the coating composition. This mixing results in increased compatibility between the NiCrAlY coating and the substrate, leading to a metallurgical bonding.…”
Section: Resultsmentioning
confidence: 99%
“…A partir deste resultado da variação da distribuição granulométrica foi possível realizar testes para a sedimentação do pó de NiCrAlY. O procedimento de sedimentação em meio líquido tem gerado resultados promissores de deposição de camadas TBC [17,18] por ser um meio simples e barato em relação ao processo de jateamento de pó juntamente ao laser, visto que o equipamento para acoplar e distribuir o pó tem um valor mais elevado de investimento e pode aumentar os períodos de manutenção pelo entupimento do canal de saída do pó pela larga distribuição de partículas.…”
Section: Discussionunclassified
“…The AISI 316 L chemical composition is described in Table I. The methodology employed in the LSP of NiCrAlY was previously described elsewhere [10]. The YSZ (ZrO 2 with 8% Y 2 O 3 ) powder (Praxair) was milled in a nylon jar, using 25 g of YSZ balls with a diameter of 1.0±0.1 mm, until it reached particle sizes smaller than 12 μm (1190L, Cilas).…”
Section: Methodsmentioning
confidence: 99%